Contributions of career planning and self-efficacy in enchancing work readiness among final year students - Andini Dwian Putri; Narastri Insan Utami; Nikmah Sofia Afiati; Amelia Cahya Kinasih (Universitas Ahmad Dahlan, 2026)
The high level of competition in the labor market and the unemployment rate among university graduates in Indonesia indicate the importance of work readiness among final-year students in facing the transition from education to employment. Therefore, it is necessary to examine internal factors that contribute to the development of work readiness in final-year students. This study aims to investigate the relationship between career planning and self-efficacy with work readiness among final-year students, both simultaneously and partially. This research employed a non-experimental quantitative correlational design using multiple regression analysis. The sampling technique used was non-probability sampling, specifically purposive sampling. Participants were active final-semester students aged 19–25 years from various disciplines and universities in Indonesia, regardless of gender. The instruments used were the Career Planning Scale, the General Self-Efficacy Scale (GSE), and the Work Readiness Scale. The results showed a significant positive relationship between career planning and work readiness among final-year students. Self-efficacy also demonstrated a significant positive relationship with work readiness. Furthermore, career planning and self-efficacy simultaneously showed a significant relationship with work readiness. These findings indicate that both career planning and self-efficacy play an important role in supporting students’ readiness to enter the workforce.